Biochemical and nutritional evaluation of patients with visceral leishmaniasis before and after treatment with leishmanicidal drugs - Gatto, Mariana [UNESP]; Abreu, Mariana Miziara De; Tasca, Karen Ingrid; Simao, Jose Claudio; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Pereira, Paulo Câmara Marques [UNESP]; Calvi, Sueli Aparecida [UNESP] (Sociedade Brasileira de Medicina Tropical - SBMT, 2013)
Introduction Visceral leishmaniasis (VL) is caused by the intracellular protozoan Leishmania donovani complex. VL may be asymptomatic or progressive and is characterized by fever, anemia, weight loss and the enlargement of the spleen and liver. The nutritional status of the patients with VL is a major determinant of the progression, severity and mortality of the disease, as it affects the clinical progression of the disease. Changes in lipoproteins and plasma proteins may have major impacts in the host during infection. Thus, our goal was evaluate the serum total cholesterol, high-density lipoprotein (HDL), low-density lipoprotein (LDL), triglycerides, glucose, albumin, globulin and total protein levels, as well as the body composition, of VL patients before and after treatment. Methods Nutritional evaluation was performed using the bioelectrical impedance analysis (BIA) to assess body composition. Biochemical data on the serum total cholesterol, HDL, LDL, triglycerides, glucose, albumin, globulin and total protein were collected from the medical charts of the patients. Results BIA indicated that both pre-treatment and post-treatment patients exhibited decreased phase angles compared to the controls, which is indicative of disease. Prior to treatment, the patients exhibited lower levels of total body water compared to the controls. Regarding the biochemical evaluation, patients with active VL exhibited lower levels of total cholesterol, HDL, LDL and albumin and higher triglyceride levels compared to patients after treatment and the controls. Treatment increased the levels of albumin and lipoproteins and decreased the triglyceride levels. Conclusions Our results suggest that patients with active VL present biochemical and nutritional changes that are reversed by treatment.
Keywords: Visceral leishmaniasis; Nutritional status; Leishmanicidal drugs